Beyond the TPP+ "gold standard": a new generation mitochondrial delivery vector based on extended PN frameworks. Issue 15 (28th March 2023) - Ong, How Chee; Coimbra, João T. S.; Ramos, Maria J.; Xing, Bengang; Fernandes, Pedro A.; García, Felipe
Abstract : PN frameworks were explored as mitochondrial delivery vectors. The newly designed phosphazenylphosphonium moiety was demonstrated to be more effective than traditional triphenylphosphonium-based vectors. Abstract : Mitochondrial targeting represents an attractive strategy for treating metabolic, degenerative and hyperproliferative diseases, since this organelle plays key roles in essential cellular functions. Triphenylphosphonium (TPP + ) moieties – the current "gold standard" – have been widely used as mitochondrial targeting vectors for a wide range of molecular cargo. Recently, further optimisation of the TPP + platform drew considerable interest as a way to enhance mitochondrial therapies. However, although the modification of this system appears promising, the core structure of the TPP + moiety remains largely unchanged. Thus, this study explored the use of aminophosphonium (PN + ) and phosphazenylphosphonium (PPN + ) main group frameworks as novel mitochondrial delivery vectors. The PPN + moiety was found to be a highly promising platform for this purpose, owing to its unique electronic properties and high lipophilicity. This has been demonstrated by the high mitochondrial accumulation of a PPN + -conjugated fluorophore relative to its TPP + -conjugated counterpart, and has been further supported by density functional theory and molecular dynamics calculations, highlighting the PPN + moiety's unusual electronic properties. These results demonstrate the potential of novel phosphorus-nitrogen based frameworks as highly effective mitochondrial delivery vectors over traditional TPP + vectors.